Sequence-based genotyping of extra-intestinal pathogenic Escherichia coli isolates from patients with suspected community-onset sepsis, Sweden. (December 2022) - Tilevik, Diana; Pernestig, Anna-Karin; Fagerlind, Magnus; Tilevik, Andreas; Ljungström, Lars; Johansson, Markus; Enroth, Helena
Abstract: Extra-intestinal pathogenic Escherichia coli (ExPEC) strains are responsible for a large number of human infections globally. The management of infections caused by ExPEC has been complicated by the emergence of antimicrobial resistance, most importantly the increasing recognition of isolates producing extended-spectrum β-lactamases (ESBL). Herein, we used whole-genome sequencing (WGS) on ExPEC isolates for a comprehensive genotypic characterization. Twenty-one ExPEC isolates, nine with and 12 without ESBL-production, from 16 patients with suspected sepsis were sequenced on an Illumina MiSeq platform. Analysis of WGS data was performed with widely used bioinformatics software and tools for genotypic characterization of the isolates. A higher number of plasmids, virulence and resistance genes were observed in the ESBL-producing isolates than the non-ESBL-producing, although not statistically significant due to the low sample size. All nine ESBL-producing ExPEC isolates presented with at least one bla gene, as did three of the 12 without ESBL-production. Multi-locus sequence typing analysis revealed a diversity of sequence types whereas phylogroup A prevailed among isolates both with and without ESBL-production. In conclusion, this limited study shows that analysis of WGS data can be used for genotypic characterization of ExPEC isolates to obtain in-depth information of clinical relevance. Highlights: WGS-based characterization of ExPEC isolates provides high-resolution information. ESBL-producing ExPEC isolates harbor more plasmids, virulence and resistance genes than non-ESBL-producing ExPEC isolates. There is a diversity of sequence types among ExPEC isolates.